EDUKASI PROGRAM REMAJA SMART: JALAN MENUJU REMAJA SEHAT, BAHAGIA, DAN BERTANGGUNG JAWAB - Chairiyah, Royani; RA, Mella Yuria; Agustina, Irwanti (Universitas Mataram, 2025)
Adolescence is a period of rapid growth and development, physically, psychologically, and intellectually. Teenagers still have limited knowledge about healthy living behaviors and the risks of negative behaviors. Improvement of Adolescent Health Knowledge and Character Through the SMART Youth Program, students will receive training on mental health, stress management, responsible decision-making, and strengthening adolescent character. The aim of this community service is to enhance teenagers' knowledge and awareness about the importance of healthy living behaviors and stress management and instill SMART character values (healthy, independent, active, religious, and responsible) in teenagers' daily lives. The activity methods were carried out through the delivery of materials, educational films, training, integration practices, and question-and-answer sessions. Topics include reproductive health, stress management, life skills, physical and social activity, ethics and religious values in adolescent life, discipline, and integrity in daily life. This activity was conducted on Wednesday, February 28, 2025, with 30 participants. The success of the activity was measured using a questionnaire. The results show an increase in knowledge from the category of sufficient knowledge to good, with teenagers increasingly understanding the importance of maintaining physical and mental health, being able to act independently, being active in positive activities, upholding religious values, and being responsible in every action. Conclusion: expanding students' knowledge and skills in facing adolescent challenges, as well as supporting the formation of a healthy, happy, and responsible adolescent character. Suggestion: It is expected to continue and integrate SMART values into learning activities and counseling guidance sustainably as part of student character development.